Efficacy of thermotherapy for herpes zoster and postherpetic neuralgia: A protocol for systemic review and meta-analysis - Li, Zhuang (Medicine (Baltimore), 2021)
BACKGROUND: Herpes zoster (HZ), is a painful skin rash disease with cutaneous symptoms and acute zoster-associated pain (ZAP). Postherpetic neuralgia (PHN), as the most frequent sequela of HZ, can persist a long time. Both HZ and PHN may significantly impact the quality of life and made great economical afford to affected patients. Its optimal treatment on HZ and PHN is still an urgent problem. In China, thermotherapy, including moxibustion and fire needle, is widely used because they can quickly promote the recovery of shingles and reduce the occurrence of PHN. Thermotherapy can also reduce pain intensity, relieve anxiety, and improve quality of life of PHN. Based on the current literatures, the effect and safety of thermotherapy will be systematically evaluated to provide appropriate complementary therapies for HZ and PHN. METHODS: Studies search for eligible randomized controlled trials (RCTs) that use thermotherapy including fire needle and moxibustion for HZ or PHN from the following databases: PubMed, EMBASE, Web of Science, the Cochrane Library, China National Knowledge Infrastructure (CNKI), China Biology Medicine Database (CBM), Technology Periodical database (VIP), and Wanfang database. Language restrictions for retrieving literature are English and Chinese. Their data extraction will be done by 2 researchers. Mean difference (MD) or relative risk (RR) with fixed or random effect model in terms of 95% confidence interval (CI) will be adopted for the data synthesis. To evaluate the risk of bias, the Cochrane's risk of bias assessment tool will be utilized. The sensitivity or subgroup analysis will also be conducted when meeting high heterogeneity (I(2) > 50%). RESULTS: This meta-analysis will provide an authentic synthesis of the thermotherapy's effect on HZ and PHN, including incidence of postherpetic neuralgia and adverse events. DISCUSSION: The findings of the review offer updated evidence and identify whether thermotherapy can be an effective treatment for HZ and PHN for clinicians. REGISTRATION NUMBER: INPLASY2020110009.